Skip to main content
Post Deleted by CommunityBot
Post Locked by CommunityBot
Post Migrated Away to cs.stackexchange.com by Kaveh
Post Closed as "off topic" by Kaveh
Source Link

Free and Bound in Lambda Calculus

Here's something from Slonneger's "Syntax and Semantics of Programming Languages":

A variable may occur both bound and free in the same lambda expression: for example, in λx.yλy.yx the first occurrence of y is free and the other two are bound.

I assume the free variable is the y right after the λx. and the bound y's are the λy.y which I can sort of intuitively grasp. So ((λx.yλy.yx)a)b) would reduce to (yλy.ya)b) then to bba ? Can someone explain how this came to be? In the end it's the expression b twice. Can someone perhaps provide more examples of bound and free variables?